Erectile Dysfunction: Key Role of Cavernous Smooth Muscle Cells - Souza, Iara Leão Luna de; Ferreira, Elba dos Santos; Vasconcelos, Luiz Henrique César; Cavalcante, Fabiana de Andrade; Silva, Bagnólia Araújo da (Frontiers in Pharmacology, 2022)
Erectile dysfunction is increasingly affecting men, from the elderly to young adults, being a sexual disorder related to the inability to generate or maintain a penile erection. This disorder is related to psychosocial factors such as anxiety, depression, and low self-esteem, to organic factors such as the presence of preexisting conditions like hypertension, diabetes and dyslipidemia. The pathophysiology of the disease is related to changes in the neurotransmission of the autonomic or the non-cholinergic non-adrenergic nervous system, as well as the release of local mediators, such as thromboxane A2 and endothelin, and hormonal action. These changes lead to impaired relaxation of cavernous smooth muscle, which reduces local blood flow and impairs penile erection. Currently, therapy is based on oral vasodilation, such as sildenafil, tadalafil, vardenafil and iodenafil, or by direct administration of these agents into the corpus cavernous or by intraurethral route, such as alprostadil and papaverine. Despite this, studies that consolidate the understanding of its pathophysiological process contribute to the discovery of new more efficient drugs for the treatment of erectile dysfunction. In this sense, in the present work an extensive survey was carried out of the mechanisms already consolidated and the most recent ones related to the development of erectile dysfunction.